Antiviral therapy substantially reduces HCC risk in patients with chronic hepatitis B infection in the indeterminate phase - Huang, Daniel Q.; Tran, Andrew; Yeh, Ming-Lun; Yasuda, Satoshi; Tsai, Pei-Chien; Huang, Chung-Feng; Dai, Chia Yen; Ogawa, Eiichi; Ishigami, Masatoshi; Ito, Takanori; Kozuka, Ritsuzo; Enomoto, Masaru; et al. (Hepatology (Baltimore, Md.), 2023)
Background and Aims: HCC risk in chronic hepatitis B (CHB) is higher in the indeterminate phase compared with the inactive phase. However, it is unclear if antiviral therapy reduces HCC risk in this population. We aimed to evaluate the association between antiviral therapy and HCC risk in the indeterminate phase. Approach and Results: We analyzed 855 adult (59% male), treatment-naïve patients with CHB infection without advanced fibrosis in the indeterminate phase at 14 centers (USA, Europe, and Asia). Inverse probability of treatment weighting (IPTW) was used to balance the treated (n = 405) and untreated (n = 450) groups. The primary outcome was HCC development. The mean age was 46±13 years, the median alanine transaminase was 38 (interquartile range, 24-52) U/L, the mean HBV DNA was 4.5±2.1 log10 IU/mL, and 20% were HBeAg positive. The 2 groups were similar after IPTW. After IPTW (n = 819), the 5-, 10-, and 15-year cumulative HCC incidence was 3%, 4%, and 9% among treated patients (n = 394) versus 3%, 15%, and 19%, among untreated patients (n = 425), respectively (p = 0.02), with consistent findings in subgroup analyses for age >35 years, males, HBeAg positive, HBV DNA>1000 IU/mL, and alanine transaminase<upper limit of normal. In multivariable Cox proportional hazards analysis adjusted for age, sex, HBeAg, HBV DNA, alanine transaminase, diabetes, and platelets, antiviral therapy remained an independent predictor of reduced HCC risk (adjusted HR = 0.3, 95% CI: 0.1-0.6, p = 0.001). Conclusions: Antiviral therapy reduces HCC risk by 70% among patients with indeterminate-phase CHB. These data have important implications for the potential expansion of CHB treatment criteria.